Separation of XRD peak profiles in single-phase metals with bimodal grain structure to analyze stress partitioning. Issue 1 (1st July 2022) - Sjögren-Levin, E; Pantleon, W; Ahadi, A; Hegedüs, Z; Lienert, U; Tsuji, N; Ameyama, K; Orlov, D
Abstract: Materials with bimodal grain size distributions have an attractive combination of strength and ductility. Harmonic structure materials are a category of bimodal-structure materials with a specific microstructure design. The deformation mechanisms of such novel materials during the early stages of deformation are not well understood. Thus, we deformed nickel with harmonic structure in tension until a true strain of 0.04 while recording powder diffraction patterns with high-energy synchrotron X-rays. Line profile analysis based on such data enables quantification of stress states and lattice defect densities in different phases in multi-phase materials. Bimodal size distributions in single-phase materials add extra complexity due to the absence of differences in composition and crystal structure causing the diffraction peaks from fine and coarse grains to appear at the same diffraction angles. Therefore, prior to any meaningful line profile analysis, the respective diffraction profiles need to be separated. A general method for automatically separating profiles originating from different grain fractions in bimodal materials is presented in this work.